Environmental management, nonmarket strategy, and firm performance in emerging markets: The case of ISO 14001. Issue 1 (23rd November 2021) - Riaz, Hammad; Saeed, Abubakr; Liedong, Tahiru Azaaviele; Rajwani, Tazeeb
Abstract: Firms use environmental management standards such as ISO 14001 to reduce the impact of business activity on the natural environment. Though these standards are widely celebrated on moral and ethical grounds, their implication for financial performance and competitiveness is equivocal. Drawing on neo‐institutional theory, we conceptualize ISO 14001 as a nonmarket strategy and examine its impact on firm performance within the contexts of three highly polluted emerging markets – China, India, and Pakistan. Employing a rigorous event‐study approach, we find that ISO 14001 certification has a negative impact on firms' operating profitability and market value in both short and long runs. This negative impact appears to be stronger in contexts with weak institutions and poor environmental protection regimes. Further multivariate analyses show that the negative impact of ISO 14001 on firm performance is weaker among socially responsible firms and stronger among politically connected firms. These findings contribute to the environmental management literature. They also have practical implications for managers.